How do you solve the following system using substitution?: - 5x + y = - 3, 3x - 8y = 24

1 Answer
May 11, 2018

x = 0 and y = -3

Explanation:

As per the question, we have

-5x + y = -3

:. y = -3 + 5x or y = 5x - 3

Now substituting the value for y in the second equation, we get

3x - 8y = 24

:. 3x - 8(5x - 3) = 24

:. 3x - 40x + 24 = 24

:. -37x = 24 -24

:. -37x = 0

:. x = 0

Now, as we know the value of x we can calculate the value of y :

y = 5x - 3

:. y = 5(0) - 3

:. y = 0 - 3

:. y = -3

Therefore, x = 0 and y = -3 are the solution to this problem.